Genetic Polymorphisms of GPX1 (rs1050450) and SOD1 (rs2070424) and the Risk of Liver Acute Rejection - Mardani, Mehrnosh; Karimi, Mohammad-Hossein; Saadat, Iraj (Scripta Medica, 2025)
Background/Aim: For patients with end-stage liver disease, a transplant is the only option. With respect to improvement of this therapeutic process, rejection occurs in 50-82 % of transplant recipients. Transplanted liver is prone to exposure acute rejection because of different reasons, such as oxidative stress. Oxidative stress with negative effect on the survival and function of transplanted tissue can cause graft rejection. Glutathione peroxidase 1 (GPX1) and superoxide dismutase 1 (SOD1) are known as antioxidant enzymes against ROS. The genetic factors can be disrupted clinical effects of the liver transplant. The aim of the research was to investigate the relationship between GPX1pro198leu and SOD1A251G polymorphisms with liver acute rejection risk in Iranian population. Methods: The genotyping of GPX1 (rs1050450) and SOD1 (rs2070424) were performed by PCR-RFLP method in 248 liver transplanted recipients as well as 253 controls. Data were analysed by SPSS statistical software. Results: The results of recipients following indicated that 58 patients experienced liver acute rejection. Analysis of the genotype in GPX1pro198leu and SOD1A251G polymorphisms between cases and controls showed no significant difference (GPX1pro198leu: OR = 1.11, 95 % CI = 0.84-1.46, p = 0.448 and SOD1A251G: OR = 1.17, 95 % CI = 0.72-1.92, p = 0.522). Moreover, result showed that genotype of these genes was not associated with incidence of acute rejection in patients with and without liver acute rejection (GPX1pro198leu: OR = 0.93, 95 % CI = 0.59-1.47, p = 0.749 and SOD1A251G: OR = 1.87, 95 % CI = 0.92-3.81, p = 0.083). Conclusions: GPX1pro198leu and SOD1A251G polymorphisms does not influence the liver diseases pathogenesis and acute rejection development in liver transplant patients. Therefore, more research is needed into the genetic factors involved in transplant recipients.